METHOD OF CARDIOVASCULAR SYSTEM ON THE BASIS OF ONE DIMENSION HAEMODYNAMICS MODEL - Yu. G. Kuzminsky; S. V. Shilko (Informatika)
A method of screening a cardiovascular system state using original software, which realizes ma-thematical analysis of oscillometry data in terms of biomechanical model of hemodynamics, is de-scribed. The screening, based on the proposed method, allows to expand the possibilities of classical oscillometry and to obtain the important information about the state of heart and blood vessels as well as the adaptability of humans (particularly, athletes) under various physiological loads.